Finite Difference Method for the One-Dimensional Non-linear Consolidation of Soft Ground Under Uniform Load - Ma, Bin-Hui; Hu, Zhi-Yong; Li, Zhuo; Cai, Kai; Zhao, Ming-Hua; He, Cheng-Bin; Huang, Xiao-Cheng (Frontiers in Earth Science, 2020)
Initial stress and additional effective stress distributions in soil greatly influence the degree of ground consolidation when calculating one-dimensional soft clay ground consolidation in deep soil. The one-dimensional nonlinear consolidation governing equations of soft ground under uniform loads are derived and solved with the finite difference method. This method is based on the assumptions that the initial stress in soil varies with the ground depth and the additional effective stress caused by external loads changes with both the ground depth and consolidation time, and the hyperbolic model of the soil stress-strain relationship. Formulas for the degree of consolidation and the settlement of the ground are presented. A case study shows that the degree of consolidation of the ground calculated with the finite difference method agrees with the traditional analytical solution, and the computational efficiency of the finite difference method can be effectively improved when the segmental calculation method is used throughout the consolidation process. The results of another example show that the settlement of the ground calculated with the finite difference method agrees with the in situ data. The suggested method can greatly simplify the consolidation calculation and has a high application value in engineering.